2018
DOI: 10.1017/jfm.2018.165
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study of laminar and transitional oblique shock wave reflections

Abstract: High-resolution particle image velocimetry measurements were performed on laminar and transitional oblique shock wave reflections for a range of Mach numbers ($M=1.6{-}2.3$), Reynolds numbers ($Re_{x_{sh}}=1.4\times 10^{6}{-}3.5\times 10^{6}$) and flow deflection angles ($\unicode[STIX]{x1D703}=1^{\circ }{-}5^{\circ }$ or $p_{3}/p_{1}=1.11{-}1.64$). The laminar interactions revealed a long, flat and triangular shaped separation bubble. For relatively strong interactions ($p_{3}/p_{1}>1.2$), the bubble grows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…In addition, when β MEP is much weaker than β FIT0 , the separation bubble should be much smaller, reducing the height of the interaction point, which might be inside of the boundary layer, as shown in figure 9(c). This configuration corresponds to relatively weak incident shock waves, and it can explain the work conducted on small angle wedges by Giepman et al (2018), who found the pressure plateau could not reach the FIT pressure rise.…”
Section: Resultsmentioning
confidence: 70%
“…In addition, when β MEP is much weaker than β FIT0 , the separation bubble should be much smaller, reducing the height of the interaction point, which might be inside of the boundary layer, as shown in figure 9(c). This configuration corresponds to relatively weak incident shock waves, and it can explain the work conducted on small angle wedges by Giepman et al (2018), who found the pressure plateau could not reach the FIT pressure rise.…”
Section: Resultsmentioning
confidence: 70%
“…While many real-world applications will be fully turbulent, laminar solutions provide useful comparisons to wind tunnel experiments where smallscale models are investigated at lower Reynolds numbers. Examples of laminar and tripped-transitional experiments in supersonic SBLI include Hakkinen et al (1959), Degrez et al (1987), Giepman et al (2015Giepman et al ( , 2016Giepman et al ( , 2018, and Diop et al (2019), in which the interactions are not fully turbulent. Furthermore, shock and expansion wave patterns are easier to distinguish in the absence of turbulence and the mechanism of transition can be investigated in laminar SBLI.…”
Section: Shockwave/boundary-layer Interactionsmentioning
confidence: 99%
“…Recent experimental studies on laminar-transitional SBLI include those of Giepman et al (2015) and Giepman et al (2018), in which a range of shock impingement locations were investigated for Mach numbers between M = [1.6, 2.3]. All experiments were performed with high-resolution PIV in a wind tunnel with a partial-span shock generator.…”
Section: Previous Studiesmentioning
confidence: 99%
“…While turbulent duct SBLI has received some attention in recent years, laminar and transitional interactions in ducts are not as well understood. The work of Giepman et al (2018) also noted experimental difficulties when seeding boundary layers in a laminar case. Numerical simulations are well placed to investigate SBLI for transitional interactions and complement existing experimental literature.…”
Section: Introductionmentioning
confidence: 99%